1998
DOI: 10.1016/s0895-7061(98)00042-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Marinobufagenin-Like and Ouabain-Like Immunoreactivity in Adrenocorticotropin-Treated Rats

Abstract: Recently, an endogenous digitalis-like factor (EDLF) was shown to be stimulated in corticotropin (ACTH) hypertension in the rat. We have shown that mammalian plasma contains a vasoconstrictor Na,K-ATPase inhibitor, which cross-reacts with an antibody to amphibian EDLF, marinobufagenin. In the present experiment, the effect of 8 days of intramuscular ACTH treatment (0.5 mg/kg/day) of male Fisher 344؋ ؋NB rats on blood pressure, plasma ouabain-like and marinobufagenin-like immunoreactivity, and on the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
(50 reference statements)
1
17
0
Order By: Relevance
“…It is interesting to note that aldosterone-induced fibrosis only appears to develop in settings where salt loading and volume expansion also occur, 38 and these settings are likely to have increased circulating concentrations of MBG. 39,40 To be sure, we noted considerable cardiac fibrosis in our renal failure model as demonstrated by histological analysis and fibronectin expression. Fourth and perhaps most important, we observed that active immunization against MBG was associated with very substantial attenuation of cardiac hypertrophy, cardiac fibrosis, and the oxidant stress state.…”
Section: Discussionmentioning
confidence: 77%
“…It is interesting to note that aldosterone-induced fibrosis only appears to develop in settings where salt loading and volume expansion also occur, 38 and these settings are likely to have increased circulating concentrations of MBG. 39,40 To be sure, we noted considerable cardiac fibrosis in our renal failure model as demonstrated by histological analysis and fibronectin expression. Fourth and perhaps most important, we observed that active immunization against MBG was associated with very substantial attenuation of cardiac hypertrophy, cardiac fibrosis, and the oxidant stress state.…”
Section: Discussionmentioning
confidence: 77%
“…The concentrations of ouabain used in Fig. 1b are much higher than those reportedly observed in the blood (20)(21)(22). Ouabain binding to Na,K-ATPase may, under physiological conditions, be expected to increase as a function of time (23).…”
Section: Low-dose Ouabain Induces [Ca 2؉ ]I Oscillationsmentioning
confidence: 70%
“…CTSs were discovered in digitalis plants and amphibian tissues (25,75). Recently, CTSs were found in the body fluids of mammals (5,23,29,73). Moreover, elevated levels of endogenous CTSs including marinobufagenin (MBG) have been associated with various pathological conditions: essential hypertension (4,24,73), preeclampsia (3,45,83), experimental diabetes (7), uremic cardiomyopathy (33), and cardiac failure (20,48,49,66,74).…”
mentioning
confidence: 99%